Servitization of global service network actors : A contingency framework for matching challenges and strategies in service transition - Reim, Wiebke; Sjödin, David R.; Parida, Vinit (Elsevier, 2019)
Servitization is a rising trend across manufacturing companies, but it is not achievable without the corresponding transition of the manufacturers’ service network. Despite the key role of service network actors, their servitization pathways are not widely understood. Thus, the purpose of this paper is to understand how diverse service network actors approach servitization under varying conditions. Findings are derived from an exploratory case study of eight service network actors for a global construction equipment manufacturer. The analysis reveals that service network actors face major capability- (lack of service provision capabilities, lack of service provision vision) and market-related challenges (unfavorable local conditions, low customer service readiness) that hinder their transformation. The analysis also reveals four unique servitization strategies (service extension, service benchmarking, digitalization, customer co-creation) that service network actors implement. A contingency framework is proposed to explain which challenges can be matched with which servitization strategies to achieve service network servitization.
Keywords: challenges; distributor; Ecosystem; Product-Service Systems (PSS); Service networks; Servitization; fi=Johtaminen ja organisaatiot|en=Management and Organization|